Microstructures, properties and preparations of lightweight refractory high-entropy alloys: A review - Gengchen Li; Zhibin Wu; Yajing Dong; Zhen Hu; Yuefei Jia; Shiwei Wu; Yongkun Mu; Kang Sun; Yandong Jia; Gang Wang (Journal of Materials Research and Technology, 2025)
Lightweight refractory high-entropy alloys (LRHEAs) have emerged as a class of advanced metallic materials, comprising multiple refractory and lightweight principal elements. These alloys exhibit a unique combination of low density and exceptional mechanical properties, particularly at elevated temperatures, making them highly attractive for applications in demanding environments such as aerospace, energy, and extreme conditions. This review presents a comprehensive overview of the research developments concerning LRHEAs over the past decade. LRHEAs are categorized into ductile and brittle categories based on their mechanical performance. The relationships between composition, microstructure, and mechanical properties are systematically analyzed. A critical examination of traditional preparation techniques, including arc melting and powder metallurgy, illuminates their respective advantages and limitations, providing a nuanced reference for future investigative directions. Additionally, the latest advancements in additive manufacturing technology are synthesized, exploring their implications for microstructural development and performance characteristics of these novel LRHEAs. Finally, the review identifies existing gaps in the research and offers prospects for the future development of LRHEAs, emphasizing the need for enhanced theoretical frameworks and novel manufacturing techniques to fully realize their potential in practical applications.